The Importance of Fulfilling Nutrition in Mothers Pregnancy at Talumelito Village - Harismayanti Harismayanti; Ani Retni; Fahmi A. Lihu (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The purpose of the counseling activity